PERANCANGAN SISTEM INFORMASI AKUNTANSI LAPORAN KEUANGAN LABA-RUGI INTEGRASI DESKTOP DAN WEBSITE PADA PD. ANUGERAH KIMIA - Dony Waluya Firdaus; Satria Putra Pamungkas; Rio Yunanto (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2012)
PD. Anugerah Kimia is located at Bumi Asri Mekar Rahayu Estate Block 5, C10, Bandung. There's when a transaction came PD. Anugerah Kimia only recorded that transaction to the sales book, nothing else. Also when they bought for merchandise inventory and expense in that compagny they only writen in payment book. In the end of a period PD. Anugerah Kimia only make Sales Statement, but not with the cost, expenses statement, and for make a sales statement they use Microsoft Excel Software. That condition can rise a risk accurating of data, and then PD. Anugerah Kimia have a problem with the sales they, they not yet get a significant growth with the customer. Based of that problem, then writer take a little "Loss-Profit Financial Statement Accounting Information System Integrated Desktop and Website At PD. Anugerah Kimia".